Astroglial Wiring is Adding Complexity to Neuroglial Networking - Giaume, Christian (Frontiers in Neuroenergetics, 2010)
Astrocytes are organized as networks of communicating cells due to their high expression level of connexins, the molecular constituents of gap junction channels. Based on their permeability properties for ions and small signaling molecules such astroglial wiring interferes with neuronal activity and survival. In this paper, I identify and discuss which future technical and conceptual progres or advances should be achieved in order to better understand how neuroglial networking contributes to brain functions and dysfunctions.